1999
DOI: 10.1149/1.1390694
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Freestanding Porous Silicon Films with High Porosities

Abstract: We have prepared noncollapsed freestanding porous silicon (ps) films with various porosities higher than 90% using electrochemical etching-electropolishing, chemical dissolving, and supercritical drying methods. For the first time, the optical absorption of ps films with porosities higher than 80% have been obtained in transmission measurements. A blue shift of the transmission curve and a sharp increase of the photoluminescence (PL) intensity with enhanced porosity have been observed. An experimental result f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Meanwhile, we also observed that the transmission at the low energy (the plateau region), T 0 , increases with porosity. The blue-shifts of the transmission are correspondent to the results given elsewhere [20][21][22][23][24][25]. Figure 2 shows four Raman spectra of the free-standing p PS films with porosities of 58, 68, 79, and 87%.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Meanwhile, we also observed that the transmission at the low energy (the plateau region), T 0 , increases with porosity. The blue-shifts of the transmission are correspondent to the results given elsewhere [20][21][22][23][24][25]. Figure 2 shows four Raman spectra of the free-standing p PS films with porosities of 58, 68, 79, and 87%.…”
Section: Resultssupporting
confidence: 80%
“…Free-standing PS films with porosities higher than 80% were prepared by the electrochemical etching-electropolishing, chemical dissolving, and supercritical drying method. A detailed description of the experimental procedure and apparatus are given in previous papers [24,25]. All of the free-standing PS films samples were oxidized in air at 200 °C for 40 or 200 h accumulatively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A study of the EL of porous Si as a function of time at a constant potential shows a redshift, 11 even though oxidation of the hydride surface of porous Si during the EL process reduces the dimension of porous Si skeleton. A more recent paper 14 shows that no notable dependence of the PL peak energy of the porous silicon has been observed upon decreasing the size of the silicon crystallites from 5.0 to 2.6 nm. To understand these recent studies, mechanisms related to the surface chemical species such as silicon hydrides have been proposed.…”
mentioning
confidence: 95%
“…The procedure was described in detail elsewhere. 14 All n-Si wafers were photoelectrochemically etched at different current densities under 80 mW/cm 2 illumination for 10 min. The porous n-Si electrode was immersed in a three-electrode, onecompartment quartz cell with a Pt coil and an Ag|AgCl reference electrode and its EL measured in 0.15 M Na 2 S 2 O 8 , 0.20 M Na 2 SO 4 , and 3.5 M C 2 H 5 OH using an Aminco Bowman series 2 luminescence spectrometer and an EG&G Princeton Applied Research Corporation model 273 potentiostat/galvanostat unit.…”
mentioning
confidence: 99%